Perancangan dan Pembuatan Situs Reseller Management pada Cargo Fashion - Enrico Siswanto (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2017)
Cargo Fashion is a small business that focuses on selling branded garments exports with the best quality and reasonable price. Cargo Fashion still has difficulty in making sales to reseller because still using manual way. Therefore, Cargo Fashion requires a website-based system that can accommodate reseller sales wherever and whenever. Website designed using Waterfall method and built using the PHP and MySQL language for the database. The results of this study is a website that can make sales for resellers and at the same time facilitate the owner of Cargo Fashion in checking the stock of goods and view sales reports. The system was tested to the owner and 100% accepted and meet all the requirements. Index Terms—reseller management, web-based application, waterfall model